Addition of sorptive mineral phases to soils decreases short‐term organic matter decomposition by reducing microbial access to substrates. (29th October 2021) - Nuñez, Jonathan; Moinet, Gabriel Y. K.; Graham, Scott L.; Turnbull, Matthew H.; Grelet, Gwen‐Aëlle; Whitehead, David
Abstract: There is increasing evidence that the accessibility of soil organic matter (SOM) to microbial decomposers is more important than chemical recalcitrance for regulating SOM stability. We show that the rapid reduction in SOM decomposition following the addition of sorptive mineral phases to soils in laboratory conditions leads to decreased accessibility of SOM to microbial decomposers due to the formation of organo‐mineral complexes. We manipulated SOM accessibility in a short‐term microcosm experiment by adding different proportions of a sorptive mineral material derived from an aluminium‐rich allophanic soil to a constant mass of soil to determine the effects on SOM decomposition after 1, 4 and 8 days. The decrease in SOM decomposition with increasing proportion of added sorptive mineral phase occurred within 1 day and did not change further at 4 and 8 days. In a second experiment, we added three proportions of the sorptive mineral phases (0%, 15% and 50%) to three soils with different carbon (C) concentrations and measured rates of SOM decomposition, changes in water extractable C, the formation of organo‐mineral complexes inferred from pyrophosphate‐extractable aluminium, and the natural abundance 13 C isotopic composition of CO2 derived from SOM decomposition. We confirmed that the proportional decreases in SOM decomposition with increasing organo‐mineral complexes and decreasing microbial access to SOM was the same for the three soils, suggesting that the effects are independent of soil C concentration and pH. We also showed that the short‐term reductions in SOM accessibility led to microbial decomposition of more 13 C enriched substrates, suggesting preferential stabilisation of plant‐derived ( 13 C depleted) substrates. Our study demonstrated that SOM accessibility and decomposition could be reduced rapidly and proportionally to the amount of added sorptive mineral phases resulting from increased organo‐mineral interactions irrespective of the initial soil organic carbon concentration. Highlights: Addition of sorptive mineral phases reduced short‐term soil organic matter (SOM) decomposition by the same proportion for three soils. Relatively 13 C depleted SOM was preferentially adsorbed onto the mineral phases. The reduction in SOM decomposition was attributed to reduced microbial access due to increased organo‐mineral interactions. The effects occurred rapidly and proportionally to the amount of added sorptive mineral phases.